2008
DOI: 10.1143/jpsj.77.105004
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Magnetic Order by Pressure in BaFe2As2

Abstract: 1)has accelerated further investigations of the related superconductors. [2][3][4] The common feature of these compounds is the possession of an FeAs layer, which is analogous to the CuO 2 plane in high-superconducting-transition-temperature (high-T c ) cuprates. Soon after the intensive investigations of the oxypnictides, the oxygen-free iron pnictide BaFe 2 As 2 5)was proposed as the next-candidate parent material of superconductors with high T c . The crystal structure of this pnictide is the ThCr 2 Si 2 -t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

21
95
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(121 citation statements)
references
References 12 publications
21
95
5
Order By: Relevance
“…The change of the transition is robust against pressure, diminishing gradually and disappearing above 10 GPa. Our present result below 8 GPa is similar to that obtained in a single crystal with a cubic anvil apparatus by Matsubayashi et al [15], and is also consistent with that previously obtained in polycrystalline samples [12]. An expanded view of resistivity above 10 GPa at low temperatures is shown in Fig.…”
Section: Fig 1: (Color Online)supporting
confidence: 93%
See 3 more Smart Citations
“…The change of the transition is robust against pressure, diminishing gradually and disappearing above 10 GPa. Our present result below 8 GPa is similar to that obtained in a single crystal with a cubic anvil apparatus by Matsubayashi et al [15], and is also consistent with that previously obtained in polycrystalline samples [12]. An expanded view of resistivity above 10 GPa at low temperatures is shown in Fig.…”
Section: Fig 1: (Color Online)supporting
confidence: 93%
“…Duncan et al have studied the difference of hydrostaticity in BaFe 2 As 2 using a piston cylinder cell, an alumina anvil cell with Daphne oil and a Bridgman anvil cell with solid steatite as pressure transmitting medium [21]. They reported that uniaxial stress strongly suppresses structural/AF ordering and induces superconductivity at lower pressure.We have studied difference of hydrostaticity in very highly hydrostatic pressure range since the confusing results appear in this region [11,12,[15][16][17]21]. We performed resistivity measurements using self-flux grown single crystals of BaFe 2 As 2 from the same batch up to 16 GPa with a cubic anvil apparatus and compared the results with those obtained with a Bridgman anvil cell containing liquid pressure transmitting medium.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…There were some reports that the 122 parent compounds AFe 2 As 2 (A = Ca, Sr, Ba, and Eu) could be tuned to SC by the application of high pressure P [2,3,4,5,6,7,8,9]. However, most of these reports were based only on resistivity measurements and hence could not establish the bulk nature of P-induced SC.…”
mentioning
confidence: 99%